Strategies to Enable Reversible Magnesium Electrochemistry: From Electrolytes to Artificial Solid–Electrolyte Interphases. (28th January 2021) - Liang, Zhiming; Ban, Chunmei
Abstract: The first prototype of a rechargeable magnesium (Mg) battery demonstrated two decades ago sparked tremendous interest in the electrochemical community due to their potential low cost, high volumetric energy density. However, the development of rechargeable Mg batteries has been hampered by the incompatibility between the Mg‐metal anode and conventional carbonate electrolytes. Research has focused on electrolytes that are thermodynamically stable against reduction at the expense of low oxidation potential at the cathode side. Alternatively, the use of an artificial solid–electrolyte interphase (SEI) via surface coating presents promising results to address the Mg/electrolyte incompatibility and significantly broaden the selection of electrolytes. This minireview discusses the limitations of electrolyte development and strategies for the design of artificial interphases in magnesium‐ion batteries. Future perspectives in the development of artificial interphases for rechargeable magnesium batteries are also discussed. Abstract : This Minireview discusses the limitations of electrolyte development and strategies for the design of artificial interphases in magnesium‐ion batteries. Future perspectives in the development of artificial interphases for rechargeable magnesium batteries are also discussed.